Characterization of YAG:Ce ceramics with graphene oxide - Deulina D. E. Darjya Evgenjevna; Paygin V. D. Vladimir Denisovich; Alishin T. R. Timofey Ruslanovich; Stepanov S. A. Sergey Aleksandrovich; Valiev D. T. Damir Talgatovich; Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Ilela A. E. Alfa Edison (2023, 2023)
Yttrium-aluminum garnet (Y3Al5O12) is an optical material that shows great potential due to its favorable light-emitting and mechanical properties, as well as its chemical stability and thermal resistance. It is commonly utilized in laser technology, optical instruments, and solid-state light sources as a result of its activation by transition metal or rare earth element ions. In this work, experiments were carried out on the procedure for compacting samples of luminescent ceramics Y3Al5O12:Ce3+, by single-base pressing followed by sintering. Comprehensive studies of the influence of graphene oxide of variable concentration (x=0.1;0.5; 1 wt.%) on the radiative characteristics of ceramic samples. It was found that the addition of graphene oxide in an amount from 0.1 to 1 wt. % affects the density and luminescent properties of YAG:Ce ceramics. There is a decrease in the value of the density parameter at concentrations of graphene oxide 0.1-1 wt. % before annealing, after annealing, the relative density value increases to ~99 %. The luminescence spectrum when excited by a blue LED chip appears as a wide band in the spectral range 460-750, the nature of which is associated with radiative transitions in the cerium ion. It has been established that the light-emitting characteristics have a downward trend when activated by graphene oxide. The integral luminescence intensity decreases from 27.1 % to 19 % with an increase in the concentration of graphene oxide.